Routine Screening for Peripartum Depression in the Gynecologic and Pediatric Setting – Evaluation of an Adapted EPDS Version - Simen, Susanne; Kuscher, Katharina; Schröder, Lea; Yilmaz-Terzioglu, Neslisah; Schröder, Torsten; Jung, Ronny; Köhler, Wolfgang; Dammer, Ulf; Kastner, Brigitte; Hillemacher, Thomas; Berg, Neeltje van den; Rauber, Susanne (Zeitschrift für Geburtshilfe und Neonatologie, 2023)
Purpose The aim of the study was to investigate the feasibility and acceptability of a routine screening for peripartum depression (PD) by gynecologists and pediatricians. In addition, it was investigated whether two separate Plus Questions (PQ) of the “EPDS-Plus” are valid for screening experiences of violence or a traumatic birth and whether they can be associated with symptoms of PD.Methods Using the EPDS-Plus the prevalence of PD was investigated in 5235 women. The convergent validity of the PQ with the Childhood Trauma Questionnaire (CTQ) and Salmon’s Item List (SIL) was assessed using correlation analysis. The association between the experience of violence and/or traumatic birth experience and PD was subjected to the chi-square test. Furthermore, a qualitative analysis for acceptance and satisfaction by the practitioners was performed.Results The prevalence was 9.94%/10.18% for antepartum/postpartum depression. The convergent validity of the PQ showed strong correlation with CTQ (p<0.001) and SIL (p<0.001). For violence and PD, a significant association was found. There was no significant association for traumatic birth experience and PD. There was a high level of satisfaction and acceptance of the EPDS-Plus questionnaire.Conclusion Screening for peripartum depression is feasible in regular care and can help to identify depressed as well as potentially traumatized mothers, especially in preparing trauma-sensitive birth care and treatment. Therefore, specialized peripartum “psych” treatment for all affected mothers in all regions has to be implemented.
Keywords: peripartum depression; EPDS-plus; violence; traumatic birth; trauma; screening